2022
DOI: 10.1177/13506501221107904
|View full text |Cite
|
Sign up to set email alerts
|

Load share model based gear loss factor prediction in high contact ratio spur gear drive

Abstract: Gear loss factor is considered to be a crucial parameter, and is governed by factors like contact load, sliding velocity, contact ratio, etc. Sliding power loss is a function of the gear loss factor and friction coefficient. It depends on the contact tooth load and its contact surfaces. A small decline in the gear loss factor and variation in the friction coefficient reduces the energy consumption which improves gear efficiency significantly. Hence, accurate prediction of the gear loss factor is important. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…From the authors past research 24,25 on the external gear teeth, it can be observed that changing the tooth shape increases the drive ability by enhancing the tooth load distribution, which in turn advances the contact and bending strength. This adjustment to the exterior gear teeth profile also lessens slippage and lowers the anticipated tooth wear depth among the drive gears.…”
Section: Prediction Of Wear In Non-standard Internal Drivementioning
confidence: 99%
“…From the authors past research 24,25 on the external gear teeth, it can be observed that changing the tooth shape increases the drive ability by enhancing the tooth load distribution, which in turn advances the contact and bending strength. This adjustment to the exterior gear teeth profile also lessens slippage and lowers the anticipated tooth wear depth among the drive gears.…”
Section: Prediction Of Wear In Non-standard Internal Drivementioning
confidence: 99%